Ayurvedic Management of Diabetic Ketoacidosis: An Integrative Review with Classical and Contemporary References - Poulose, Pouse; Resmi, K K (International Research Journal of Ayurveda & Yoga, 2025)
Diabetic ketoacidosis (DKA) is a serious and potentially life-threatening complication of uncontrolled diabetes mellitus. It manifests as hyperglycemia, ketonemia, and metabolic acidosis. Conventional management relies heavily on fluid resuscitation, insulin therapy, and electrolyte correction. However, Ayurveda offers a complementary framework that addresses the underlying metabolic dysfunction, focusing on doshic imbalances, impaired digestion (Agnimandya), and toxin accumulation (Āma). This review explores the Ayurvedic correlation of DKA with Madhumeha, outlines classical treatment protocols, and highlights opportunities for integration with modern medical strategies. The article draws from over 25 classical and peer-reviewed modern sources to ensure an evidence informed and plagiarism-free presentation.